A structure-based catalytic mechanism for the xanthine oxidase family of molybdenum enzymes - Huber, Robert (1996)
The crystal structure of the xanthine oxidase-related molybdenum-iron protein aldehyde oxidoreductase from the sulfate reducing anaerobic Gram- negative bacterium Desulfovibrio gigas (Mop) was analyzed in its desulfo-, sulfo-, oxidized, reduced, and alcohol-bound forms at 1.8-Å resolution. In the sulfo-form the molybdenum molybdopterin cytosine dinucleotide cofactor has a dithiolenebound fac-[Mo, =O, =S, ···(OH2)] substructure. Bound inhibitory isopropanol in the inner compartment of the substrate binding tunnel is a model for the Michaelis complex of the reaction with aldehydes (H-C=O, -R). The reaction is proposed to proceed by transfer of the molybdenum-bound water molecule as OH- after proton transfer to Glu-869 to the carbonyl carbon of the substrate in concert with hydride transfer to the sulfido group to generate [MoIV, =O, -SH, ···(O-C=O, -R)). Dissociation of the carboxylic acid product may be facilitated by transient binding of Glu- 869 to the molybdenum. The metal-bound water is replenished from a chain of internal water molecules. A second alcohol binding site in the spacious outer compartment may cause the strong substrate inhibition observed. This compartment is the putative binding site of large inhibitors of xanthine oxidase.